KEPENTINGAN KEAMANAN NASIONAL RUSIA DALAM SERANGAN MILITER TERHADAP UKRAINA TAHUN 2022 - Emanuel Sani de Ornay; Nur Azizah (Universitas Bung Karno, 2022)
ABSTRACT This study wants to find out how the background that influences Russia to carry out a military attack on Ukraine in 2022 and study Russia's national security interests against Ukraine. Russia is making changes to its military policy in Ukraine by increasing the number of military equipment and soldiers and carrying out military attacks in 2022. The purpose of this study is to analyze the factors that influence or become the background of Russia in carrying out military attacks and their relationship to its national interests. The theoretical framework used in this research is the concept of national interest described by H.J Morgenthau, and foreign policy from Morgenthau. The concept of national interest and foreign policy is used to explain the factors that influence Russia in carrying out its 2022 military attack policy in Ukraine and its relationship with its national interest in selfdefense. In its policy, Russia is increasingly intensive in sending military personnel and equipment to support military operations in Ukraine. Russia, then also changed its strategy in the operation where in its operation Russia was more offensive and Russiaalso divided the area of operation between the North and the South. From the results of the author's analysis using the theoretical framework, it can be concluded that Russia's military policy related to the political crisis in Ukraine is caused by internal factors, the existence of national interests that must be protected and external factors in the form of the source system behind it. These national interests are related to defense, economy, politics and the military. While the external factor is the existence of a source system where there is a pattern ofinteraction or alliances that exist in the Eastern European region and the security of the country is threatened. The author finds that Russia is trying very hard in carrying out its military policy in order to protect its nation. Keywords: Russia, Ukraine, National Interest